MORPHOMETRIC MEASUREMENT AS AN INDEX FOR ESTIMATING YIELD OF MEAT IN SHELL 2.MUSSEL (PERNA VIRIDIS) AND CLAM (VILLORITA CYPRINOIDES) - GEORGE, CHINNAMMA; UNNITHAN, G RAJAGOPALAN; GOPAKUMAR, K (Fishery Technology, 2017)
Observations (76 nos) on height-length and whole weight-meat weight relations of mussels (Perna viridis), both wild and cultured were made. From the length of mussel the height can be worked out by the equations (logarithmic scale),1. y = 0.360 + 0.988 x for wild2. y = 0.334 + 1.011 x for cultured,where xis the length (cm) and y is the height (ems). So also to any height the corresponding meat weight can be obtained by the regression equation.log w = -0.8178 + 1.9769 log H for wild variety (1)log w = -1.3049 + 2.8385 log H for culture-variety (2) where w is the meat weight (g) and H is the height (cm) of the mussel. F o urte.en observations on sizeweight measurements of dams were made. The yield varied from 8.9 to 13%. The length-height relationship worked out for clams (Villorita sp) is y=0.485+ 1.005 x for length x and height y.